Pengaruh Strategi Logistik Terhadap Kinerja Perusahaan - Sulida Erliyana; M Aji Luhur Pambudi (JURNAL TRANSMA, 2025)
Logistics is one of the important elements in the supply chain that plays a significant role in increasing the competitiveness of companies. This article examines how an effective logistics strategy can improve a company's performance both in terms of operations and finances. This research focuses on logistics strategies such as distribution optimization, the use of information technology in supply chain management, and collaboration with third parties. This study uses a descriptive research method with a qualitative and quantitative approach (mixed method). This approach was chosen to comprehensively analyze and describe the company's logistics strategy. The results of the study show that the right logistics strategy can lower operational costs, increase efficiency, and strengthen customer satisfaction, which ultimately has a positive impact on the company's performance.